The role of tannins in forage legumes - Piluzza G.; Bullitta S.; Re G.A.; Sulas L. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Plant tannins, polyphenolic secondary compounds, are synthesized to meet ordinary physiological demands of plants and as a response to biotic and abiotic stress. Tannins have been described as having adverse or beneficial effects, depending on their concentration and structure, plant source and the species, physiological state and diet of the animals. Proper concentrations of condensed tannins (20 – 50 g kg-1 of DM) are expected to increase the efficiency of protein digestion and to minimize detrimental effects associated with a heavy load of internal parasites, with positive consequences for animal performance and health. Moreover, lower CH4 emissions by ruminants consuming forages containing low levels of condensed tannins were noticed. This paper reports an update of current use of legume tannins in feedstuff and their effects in animals. It also refers to the implications concerning the improvement of nutrient utilization and the environmental sustainability in meat and dairy farming.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)